DINAMIKA SALINITAS DAN KANDUNGAN LOGAM BERAT KADMIUM (CD) DI EKOSISTEM MANGROVE: STUDI KASUS DI MANGUNHARJO, SEMARANG - Nahdah, Sarah Fatimah; Hartini, Eko; Mentari, Alvi Eka (Dian Nuswantoro Semarang, 2025)
Cadmium (Cd) in surface water is classified as one of the pollutants that can lead to contamination of the aquatic ecosystem. Cadmium can originate from industrial waste, agriculture, and other human activities. Mangunharjo Beach is a mangrove vegetation area located in Mangunharjo Village, Tugu District, Semarang City, Central Java. Mangrove plants can absorb heavy metals present in the water. The purpose of this research is to determine the content of Cd heavy metal in the water and its contamination of mangrove plants. The type of research in this study is observational. The samples used are seawater and mangrove plant leaves taken from three sampling points in the Mangunharjo Mangrove Coast area. Salinity measurement is done using a salinity meter, while cadmium measurement is done using ICP-OES (Inductively Coupled Plasma – Optical Emission Spectrometry). The research findings indicate that the highest concentrations of heavy metal cadmium in seawater and mangrove leaf tissues from the Mangunharjo waters are 0328 mg/l and 0197 ppm. The salinity level of the water does not affect the concentration of cadmium (Cd) in both seawater and mangrove plants. However, the high concentration of cadmium (Cd) in seawater does impact the cadmium content in mangrove plants. The cadmium (Cd) content in the seawater in the Mangharjo coastal area has exceeded the quality standard set by Government Regulation of Republic Indonesia No. 22 of 2021, which is 0,002 mg/l. Efforts are needed to conserve the local mangrove area in order to reduce coastal erosion and minimize the risk of tidal flooding in Mangunharjo Village.